Sweden - from macroeconomic failure to macroeconomic success - Calmfors, Lars (Munich, 2012)
"Major economic reforms have been carried through in Sweden during the last two decades. Most of the reforms have been made in response to long-standing rather than to acute problems. There has usually been a strong perception among economists, policy makers and the general public of the problems that the reforms have sought to address. Reforms in other countries have sometimes provided inspiration. Most of the reforms were based on a broad political consensus. A heavy input from economic research has often been used as a basis for change."